Pemberian Asuhan Keperawatan pada Masa Pandemi Covid-19 di Ruang Rawat Inap - Megawati Kristina Parapat; Wan Nishfa Dewi; Sri Wahyuni (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2022)
The spread of the coronavirus and the increasing number of Covid cases with various symptoms shown by Covid-19 sufferers are a challenge for nurses in providing nursing services. This study aimed to determine the provision of nursing care delivery during the Covid-19 pandemic. This study employed a descriptive study design. The sample involved was 80 respondents selected using a simple random technique. The nursing care process was collected using a questionnaire that tested its validity and reliability. Data were analyzed using univariate analysis, describing respondents' characteristics and components of nursing care. The results of this study found that the majority of respondents were aged 30 – 45 years (76.2%), female (90%), had a Diploma in nursing education (48.8%) and had working experience of 6-12 years (48.8%). Results of the nursing care have a suitable category consisting of assessment (53,8%), diagnosis (55%), intervention (55%), implementation (58.8%), and evaluation (58.8%). The provision of nursing care during Covid-19 has been carried out satisfactorily. However, this implementation has not reached the Indonesian Ministry of Health standards in providing nursing care.